Vascular architecture characters and risk factors analysis of unstable moyamoya disease - Zhao, Liming; Wu, Ruiyu; Xue, Bingqian; Gao, Tao; Liu, Yang; Sun, Yuxue; Guo, Gaochao; Li, Tianxiao; Li, Chaoyue (Frontiers in Neurology, 2024)
Background In some MMD patients, the digital subtraction angiography (DSA) examination found, occlusion in the ipsilateral internal carotid artery or middle cerebral artery, accompanied by the formation of numerous moyamoya vessels. Conversely, the contralateral internal carotid artery or middle cerebral artery shows signs of stenosis without the presence of moyamoya vessels. Notably, cerebral perfusion studies reveal a similar or even more severe reduction in perfusion on the occluded side compared to the stenotic side. Importantly, clinical symptoms in these patients are typically attributed to ischemia caused by the stenotic side. This condition is referred to as unstable moyamoya disease (uMMD). Objective This clinical research focuses on evaluating risk factors related to MMD and developing strategies to minimize postoperative complications. The study aims to analyze vascular characteristics and identify potential risk factors in patients with uMMD. Methods The authors reviewed consecutive cases with complete clinical and radiological documentation of patients who underwent surgery between January 2018 and June 2023. Univariate analysis and multivariate logistic regression analysis were employed to understand the risk factors and prognosis of postoperative complications in uMMD. Results Postoperative complications were retrospectively analyzed in 1481 patients (aged 14 to 65). Among them, 1,429 patients were assigned to the conventional treatment group, while 52 were in the unstable moyamoya disease group. The uMMD treatment group showed a significantly higher incidence of early postoperative complications such as RIND, cerebral infarction, and cerebral hemorrhage (p < 0.05). Univariate and multivariate logistic regression analyses were conducted on the postoperative complications of 52 uMMD patients. Initial symptoms of stenosis ≤50% (univariate: p = 0.008, multivariate: p = 0.015; OR [95% CI] =23.149 [1.853–289.217]) and choosing occluded side surgery (univariate: p = 0.043, multivariate: p = 0.018; OR [95% CI] =0.059 [0.006–0.617]) were identified as significant risk factors for postoperative neurological complications. Conclusion Compared to the conventional treatment group, uMMD has higher complication rates, with vascular stenosis degree and surgical side selection identified as significant risk factors. A comprehensive understanding of preoperative clinical symptoms and vascular characteristics in moyamoya disease patients, coupled with the formulation of rational surgical plans, contributes positively to decreasing postoperative mortality and disability rates in uMMD.